Penentuan standard maslahah dan mafsadah dalam rawatan materniti di Malaysia / Siti Khatijah Ismail - Siti Khatijah, Ismail (2017)
Maternity treatment refers to medical procedures on women during antenatal care, labour and childbirth (intrapartum) and following childbirth (postpartum). In view of the maqasid al-shari„ah, some of the treatment procedures demonstrate conflicting notions between maslahah and mafsadah. Apparently, different interpretations of the concept of maslahah and mafsadah have led to different application of both terms in the derivation of rulings process based on the current context. This has also led to confusion in determining the standard of maslahah and mafsadah during the maternity treatment. Consequently, the confusion has not only caused ambiguity in assessing the ruling of current maternity practices, but has also caused misconduct and breach of the medical code of ethics due to inaccurate application of the concept of maslahah and mafsadah. Therefore the study assesses the extent to which the maternity treatment in Malaysia complies with the maqasid al-shari‘ah through the application of the concept of maslahah and mafsadah. In addition, the study aims to suggest approaches in determining the standard of maslahah and mafsadah in its application. This is to ensure that the application meets the maslahah of the women and their foetus, and subsequently preventing from the infliction of mafsadah. To obtain the necessary data, library research method and semi-structured interviews were conducted. Meanwhile, data analysis was conducted based on the methods of inductive, deductive and comparative approach. The study found that in certain issues, Muslim scholars applied the concept of al-muwazanah and al-tarjih in determining the element of maslahah and mafsadah. The study also found that the general guidelines and manual for maternity treatment procedures in Malaysia are in conformity with the maqasid al-shari‘ah. However, certain treatment procedures require the determination of a specific (juz‟i) standard of maslahah and mafsadah. Thus, there are two approaches identified to solve the problem which are; the first is to identify the status of the medical indication in the perspective of maqasid al-shari‘ah, and the second is to determine the level of risk factor whether it is wahm, ghalabah al-zan or qat'i. Both of these approaches adopt the concept of the relationship between wasail and tawabi„ with maqasid.